Allpass based on a generalized divider principle - Ticha, Dasa (Communications - Scientific letters of the University of Zilina, 2004)
This paper deals with a new allpass structure based on a generalized divider principle. An efficient modification of the basic general divider structure using Antoniou’s GICs is presented and the corresponding 1st- and 2nd-order allpass circuits are derived. A detail discussion is devoted to the optimized design of the 2nd-order allpass, taking minimization of the active elements nonidealities and dynamics optimization into account. An original design procedure is described and documented on numerical examples.